Pemahaman Guru Sekolah Dasar terhadap Universal Design for Learning sebagai Strategi Belajar yang Mendukung Pendidikan Inklusif - Grahita Kusumastuti; Wening Prabawati (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research aims to determine elementary school teachers' understanding of universal design for learning (UDL) in inclusive classrooms. This research used a quantitative research approach with a survey design. Participants included thirty-two teachers at the elementary school level who have students with disabilities in their classes. Data was collected by conducting a survey using an instrument developed based on literature regarding universal design for learning strategies. The instrument has twenty-three items about the concept and implementation of three aspects of universal design for learning, such as multiple engagement, multiple representations, and multiple actions and expressions. The collected data was analyzed using statistical techniques such as frequency distribution, standard deviation, and one-way ANOVA. The findings show that elementary school teachers have a low level of knowledge regarding universal design for learning. Moreover, there was no statistically significant difference in teachers' understanding of universal design for learning based on years of teaching experience, highest degree earned, or gender. This research also suggests future research with a large sample and analysis.